2023
DOI: 10.1002/eap.2868
|View full text |Cite
|
Sign up to set email alerts
|

Increasing stability of a native freshwater fish assemblage following flow rehabilitation

Abstract: Stream restorations are increasingly critical for managing and recovering freshwater biodiversity in human-dominated landscapes. However, few studies have quantified how rehabilitative actions promulgate through aquatic communities over decades. Here, a long-term dataset is analyzed for fish assemblage change, incorporating data pre-and post-restoration periods, and testing the extent to which native assemblage stability has increased over time. In the late 1950s, a large capacity dam was installed on Putah Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
(144 reference statements)
0
3
0
Order By: Relevance
“…Although there are more than a hundred wildlife rehabilitation centers worldwide, there are fewer rehabilitation centers for marine mammals. Rehabilitation centers for fish that live in natural environments, but are transferred to aquariums, are limited due to insufficient expert veterinarians and staff [11]. Therefore, diseases in larger fish species are mostly treated simply and empirically; if the treatment fails, new fish are caught to replace the deceased fish.…”
Section: Is Fish Rehabilitation Effective In Aquariums?mentioning
confidence: 99%
“…Although there are more than a hundred wildlife rehabilitation centers worldwide, there are fewer rehabilitation centers for marine mammals. Rehabilitation centers for fish that live in natural environments, but are transferred to aquariums, are limited due to insufficient expert veterinarians and staff [11]. Therefore, diseases in larger fish species are mostly treated simply and empirically; if the treatment fails, new fish are caught to replace the deceased fish.…”
Section: Is Fish Rehabilitation Effective In Aquariums?mentioning
confidence: 99%
“…In a recent review, Bouska et al (2023) suggested tributaries may provide ideal opportunities for native fish conservation, relative to actions targeting main-stem rivers, due to the potential for isolation of tributaries from invasive predators or competitors, relative effectiveness of invasive species control, reduced monitoring effort required to assess management outcomes, and fewer competing objectives among managers, landowners, and stakeholders that may limit consensus building. Conservation strategies may include reintroductions or population enhancements, habitat protection, or implementation of tributary environmental flows (e.g., Jacinto et al 2023), among others. These strategies may be informed and prioritized by an improved understanding of spatial variability in demographic rates and the degree to which rates are synchronized across space and time (Cooke et al 2016), as well as the magnitude and sources of recruitment to main-stem river populations (Schindler et al 2010;Tsuboi et al 2022;Bouska et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Conservation strategies may include reintroductions or population enhancements, habitat protection, or implementation of tributary environmental flows (e.g., Jacinto et al. 2023), among others. These strategies may be informed and prioritized by an improved understanding of spatial variability in demographic rates and the degree to which rates are synchronized across space and time (Cooke et al.…”
Section: Introductionmentioning
confidence: 99%
“…According to available long-term studies, e-flows most often have a positive effect on river ecosystems and the fish populations they support. For example, providing more flow can result in greater richness and abundance of macrophyte species (Staentzel et al 2018), macroinvertebrate communities (Growns 2016;Pander et al 2019), and fish communities (Kiernan et al 2012;Pander et al 2019;Jacinto et al 2023). However, the benefits of e-flows can be considerably reduced or even eliminated if the flows are not adequate (Arthington et al 2006;Bradford et al 2011;Ceola et al 2018;Ryan et al 2021) or if the flow targets are not met (Pennock et al 2022).…”
Section: Introductionmentioning
confidence: 99%